Analisis Laju Paparan Radiasi Berdasarkan Variasi Jarak Radiografer - Nandira Abrar Arifien 2302180063; Lili Julia Rahmat; Surdiyah Asriningrum; Oktarina Damayanti (Bandung Conference Series: Medical Science, 2026)
Abstract. Radiation protection is a critical aspect of occupational safety for radiographers, one of which involves maintaining an appropriate distance from the radiation source in accordance with the ALARA principle. The use of wired exposure switches and remote exposure switches during mobile X-ray examinations results in variations in the radiographer’s distance from the radiation source, which can affect the exposure rate. This study aims to analyze radiation exposure rates based on variations in the distance between the radiographer and the radiation source in the mobile X-ray examination room at the Radiology Department of Koja Regional General Hospital in North Jakarta. This study employed a quantitative descriptive method with a correlational approach. Measurements were taken using a calibrated Fluke Biomedical survey meter at three measurement points (A, B, and C) at distances of 2 m, 3 m, 4 m, and 5 m, using a Thoraks exposure factor of 59 kV and 8 mAs. Five measurements were taken at each point; the data were then analyzed using IBM SPSS Statistics version 31 and compared with the provisions of BAPETEN Regulation No. 4 of 2013. The results of the study show that the average radiation exposure rate at a distance of 2 m was 0.23–0.30 μSv/hour, at 3 m was 0.53–0.65 μSv/hour, at 4 m was 0.36–0.57 μSv/hour, and at 5 m was 0.25–0.34 μSv/hour. All results remain below the safety limit of 0.68 μSv/hour. Correlation tests indicate a very strong negative relationship (r = -0.853 to -0.924), meaning that as the distance from the radiation source increases, the radiation exposure rate tends to decrease. Abstrak. Proteksi radiasi merupakan aspek penting dalam keselamatan kerja radiografer, salah satunya melalui pengaturan jarak terhadap sumber radiasi sesuai prinsip ALARA. Penggunaan wired exposure switch dan remote exposure switch pada pemeriksaan Mobile X-Ray menyebabkan variasi jarak radiografer dari sumber radiasi yang dapat memengaruhi laju paparan. Penelitian ini bertujuan menganalisis laju paparan radiasi berdasarkan variasi jarak antara radiografer dengan sumber radiasi pada ruang pemeriksaan Mobile X-Ray di Instalasi Radiologi RSUD Koja Jakarta Utara. Penelitian menggunakan metode deskriptif kuantitatif dengan pendekatan korelasi. Pengukuran dilakukan menggunakan survey meter Fluke Biomedical yang telah dikalibrasi pada tiga titik pengukuran (A, B, dan C) dengan variasi jarak 2 m, 3 m, 4 m, dan 5 m menggunakan faktor eksposi Thoraks 59 kV dan 8 mAs. Setiap titik dilakukan lima kali pengukuran, kemudian data dianalisis menggunakan IBM SPSS Statistics versi 31 dan dibandingkan dengan ketentuan BAPETEN Nomor 4 Tahun 2013. Hasil penelitian menunjukkan rata-rata laju paparan radiasi pada jarak 2 m sebesar 0,23–0,30 μSv/jam, 3 m sebesar 0,53–0,65 μSv/jam, 4 m sebesar 0,36–0,57 μSv/jam, dan 5 m sebesar 0,25–0,34 μSv/jam. Seluruh hasil masih berada di bawah batas aman 0,68 μSv/jam. Uji korelasi menunjukkan hubungan negatif yang sangat kuat (r = -0,853 sampai -0,924), sehingga semakin jauh jarak dari sumber radiasi, laju paparan radiasi cenderung menurun.